Co-Stimulatory Molecules during Immune Control of Epstein Barr Virus Infection - Christian Münz (Biomolecules, 2021)
The Epstein Barr virus (EBV) is one of the prominent human tumor viruses, and it is efficiently immune-controlled in most virus carriers. Cytotoxic lymphocytes strongly expand during symptomatic primary EBV infection and in preclinical in vivo models of this tumor virus infection. In these models and patients with primary immunodeficiencies, antibody blockade or deficiencies in certain molecular pathways lead to EBV-associated pathologies. In addition to T, NK, and NKT cell development, as well as their cytotoxic machinery, a set of co-stimulatory and co-inhibitory molecules was found to be required for EBV-specific immune control. The role of CD27/CD70, 4-1BB, SLAMs, NKG2D, CD16A/CD2, CTLA-4, and PD-1 will be discussed in this review. Some of these have just been recently identified as crucial for EBV-specific immune control, and for others, their important functions during protection were characterized in in vivo models of EBV infection and its immune control. These insights into the phenotype of cytotoxic lymphocytes that mediate the near-perfect immune control of EBV-associated malignancies might also guide immunotherapies against other tumors in the future.